The association between sense of humour and trauma-related mental health outcomes: two exploratory studies - Boerner, Michaela; Joseph, Stephen; Murphy, David (Taylor & Francis (Routledge), 2017)
Two studies (n = 73, n = 132) explored the association between sense of humour and trauma related well-being outcomes. It was found that sense of humour was not associated with reports of posttraumatic growth as measured by the Posttraumatic Growth Inventory (PTGI). Self-enhancing humour was positively associated with positive changes as measured by the CiOQ-P. Benign humour styles were associated negatively with emotion regulation difficulties and negative changes (CiOQ-N). Self-defeating humour was associated positively with negative changes, avoidant states and emotion regulation difficulties. The results suggest that self-enhancing humour could be helpful in order to cope with trauma.